Comparative Efficiency of Some Novel Insecticides against Fall Army Worm, Spodoptera frugiperda in Maize - Zaman, Md Imraj; Patel, Lakshman Chandra (International Journal of Bio-resource and Stress Management, 2023)
The present study was carried out at the instructional farm, College of Agriculture, Bidhan Chandra Krishi Viswavidyalaya, Farm Gate, Kalna Road, Burdwan Sadar, West Bengal, India for successive 2 terms of crop during kharif (June to September, 2020) and rabi (December to March, 2020–21). The bio-efficacy of some chemicals (Cyantraniliprole, Chlorantraniliprole, Emamectin benzoate, Flubendiamide, Spinosad, Emamectin benzoate, Broflanilide, Chlorfenapyr, Spinetoram and Teflubenzuron) and bio-pesticides (Bacillus thuringiensis var kurstaki, Beauveria bassiana, Metarhizium anisopliae, Azadirachtin and Steinernema sp.) were evaluated against Fall Army Worm (FAW) in corn at the field condition. The major parameters considered for comparing the treatments were based on percent reduction in larval population, leaf damage (%) followed by headonic scoring (0–9 scale) and attack intensity (%). All the chemical insecticides except teflubenzuron resulted more or less higher percent population reduction of FAW larva (75.39–89.17%), lower leaf damage (20.13–31.21%) along with low damage score (1.45–1.95) and lower attack intensity (3.03–6.09%). All these effects were at moderate range in case of bio-pesticides. Based on the present findings, better selection of suitable insecticides is possible to manage FAW in corn.